2021
DOI: 10.2147/jmdh.s326962
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Anemia and Associated Factors Among Term Newborns in Nekemte Specialized Hospital, Western Ethiopia

Abstract: Background Anemia is a global public health problem that affects approximately one-third of the global population. Infants and children are the ones to develop both short-term and long-term devastating complications from anemia. Although anemia is a very big public health concern, newborns, especially in developing countries, are usually overlooked and undiagnosed. Purpose The aim of this study was to assess the prevalence of anemia and associated factors among term new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…For every 1-point increase in maternal hemoglobin, there was a corresponding 0.14-point increase in umbilical cord hemoglobin. The finding of a positive correlation between maternal and umbilical cord hemoglobin in this study is similar to other studies in Nepal, Kenya, Ethiopia, Israel, India, and Iran [ 22 25 ]. Since the fetus obtains iron from maternal transferrin, when maternal iron stores are depleted, the fetus cannot accumulate as much iron, resulting in a decrease in fetal iron stores and reduced fetal hemoglobin levels [ 10 , 26 29 ].…”
Section: Discussionsupporting
confidence: 91%
“…For every 1-point increase in maternal hemoglobin, there was a corresponding 0.14-point increase in umbilical cord hemoglobin. The finding of a positive correlation between maternal and umbilical cord hemoglobin in this study is similar to other studies in Nepal, Kenya, Ethiopia, Israel, India, and Iran [ 22 25 ]. Since the fetus obtains iron from maternal transferrin, when maternal iron stores are depleted, the fetus cannot accumulate as much iron, resulting in a decrease in fetal iron stores and reduced fetal hemoglobin levels [ 10 , 26 29 ].…”
Section: Discussionsupporting
confidence: 91%
“…Most of the above studies did not assess important risk factors for neonatal anemia like maternal and obstetric conditions (APH, multiple pregnancy, HIV/AIDS, and Malaria), 9 , 22 and used the cord blood for hemoglobin value, unlike the current study. In all the studies done in Ethiopia, only term neonates were included 9 , 22 , 23 whereas only preterms were included in Bosnia. 13 None of the studies included the entire neonatal period, which could affect the prevalence of anemia in the newborn due to physiological reduction of hemoglobin in the postnatal life.…”
Section: Discussionmentioning
confidence: 99%
“…The risk factors for neonatal anemia also vary depending on the settings. 7–9 , 13 , 15 , 21 In previous studies, contributing factors for neonatal anemia included maternal anemia, 7 , 8 , 22 maternal malaria attack during pregnancy, 7 , 21 maternal antepartum hemorrhage (APH), 7 , 23 lack of iron-folate supplements during pregnancy, 23 maternal vegetable consumption habit, 9 septicemia in the newborn, 7 , 16 prematurity 13 and other neonatal problems including external blood loss. 15 , 16…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, those studies found that anemia in the mother, mothers' age, preterm birth, her habit of consuming vegetables, cesarean delivery, occupation, parasitic infection, vaginal bleeding during pregnancy and her failure to take iron/folate supplements during her pregnancy were all associated with newborn anemia. [10][11][12] In a newborn, anemia is a common and complex problem owing to the unique blood picture because of variations in hematological profiles. 13 It may result in an acute, severe, or asymptomatic life-threatening event.…”
Section: Introductionmentioning
confidence: 99%